Narrowing the Development Divide in ASEAN: The Role of Policy - Jayant Menon (Asian Development Bank (ADB), 2012)
The Association of Southeast Asian Nations (ASEAN) is highly diverse. It is also divided. The most striking example is the development divide that separates ASEAN's newer members of Cambodia, the Lao People's Democratic Republic, Myanmar, and Viet Nam—the CLMV countries—from the organization's original members, or ASEAN-6. More rapid growth in Cambodia, Lao People's Democratic Republic, and Viet Nam since the 1990s—driven by trade, investment, and other market reforms—has reduced income differences between this grouping and ASEAN-6. Yet, while the development divide has narrowed, huge gaps remain. The further narrowing of these gaps will require an increase in the pace and breadth of policy reforms, and start addressing labor mobility. Although rapid growth has resulted in convergence among ASEAN members, it has also increased polarization within individual countries. This can threaten social cohesion and the sustainability of future growth. There is a pressing need to invest more in education and health, and to institute land reform.
hdl:11540/1303
Keywords: F15; O24; 330; ASEAN; development divide; convergence; inequality; transition economies; labor mobility; Wirtschaftliche Konvergenz; Entwicklungspolitik; Arbeitsmigranten; Transformationsstaaten; ASEAN-Staaten